Mr. Fox's game of "No!" [book with audioplayer] - LaRochelle, David (Candlewick Press, 2024)
"Can you beat Mr. Fox at his Game of No? The rules are simple: every time he asks a question, you must respond with 'NO.' If you accidentally say 'YES,' then it's back to the beginning of the book for you, where you must start all over again"--